Ultrathin, Soft, Bioresorbable Organic Electrochemical Transistors for Transient Spatiotemporal Mapping of Brain Activity - Wu, Mengge; Yao, Kuanming; Huang, Ningge; Li, Hu; Zhou, Jingkun; Shi, Rui; Li, Jiyu; Huang, Xingcan; Li, Jian; Jia, Huiling; Gao, Zhan; Wong, Tsz Hung; et al. (Advanced science, 2023)
A critical challenge lies in the development of the next‐generation neural interface, in mechanically tissue‐compatible fashion, that offer accurate, transient recording electrophysiological (EP) information and autonomous degradation after stable operation. Here, an ultrathin, lightweight, soft and multichannel neural interface is presented based on organic‐electrochemical‐transistor‐(OECT)‐based network, with capabilities of continuous high‐fidelity mapping of neural signals and biosafety active degrading after performing functions. Such platform yields a high spatiotemporal resolution of 1.42 ms and 20 µm, with signal‐to‐noise ratio up to ≈37 dB. The implantable OECT arrays can well establish stable functional neural interfaces, designed as fully biodegradable electronic platforms in vivo. Demonstrated applications of such OECT implants include real‐time monitoring of electrical activities from the cortical surface of rats under various conditions (e.g., narcosis, epileptic seizure, and electric stimuli) and electrocorticography mapping from 100 channels. This technology offers general applicability in neural interfaces, with great potential utility in treatment/diagnosis of neurological disorders. The ultrasoft, multichannel, biodegradable OECT‐based neural interfaces are developed, which not only monitor the μ‐ECoG signals in high fidelity, but also autonomous degradation without any trigger events. Arrays with 100 channels, temporal/spatial resolution of 1.42 ms and 20 µm, and great signal‐to‐noise ratio of 37 dB, are achieved, demonstrating a facile and efficient tool for diagnostic purposes and neuroscience research.